Women's Leadership: Building Values Of Tolerance And Equality In Early Childhood Education Institutions - Hofiyatun Nisa; Ita Nurmalasari; Ida Faridah (Fakultas Tarbiyah Dan Ilmu Keguruan Institut Agama Islam An-Nawawi Purworejo, 2023)
The involvement of women leaders, especially in early childhood education, is essential to the nature of a woman who is soft, patient, and affectionate, making children feel more comfortable in building deeper social emotions such as tolerance and equality. This study aims to analyze and understand women's leadership in building values of tolerance and equality in early childhood. The location of study was conducted in PAUD Asmaul Husna, Sogaan, Pakuniran Probolinggo. This research uses a qualitative approach type of case study. The results showed that, first, the leadership in PAUD Asmaul Husna is a woman who is highly dedicated to creating polite cultural programs to develop a solid foundation to build intelligence, values, tolerance, and equality in children's souls. Second, applying the values of tolerance and equality has been carried out in PAUD Asmaul Husna with the following stages: first, SWOT Analysis. Second, the implementation of religious moderation programs. Third, Innovators and Motivators. Fourth, gender awareness for early childhood. The involvement of women leaders in building tolerant and equality values applied through religious moderation programs can provide early stimulation of understanding tolerance and equality, which will be the basis for future knowledge of child growth